Thermal Structure and Aerosols in Mars' Atmosphere From TIRVIM/ACS Onboard the ExoMars Trace Gas Orbiter: Validation of the Retrieval Algorithm. Issue 2 (15th February 2022) - Guerlet, S.; Ignatiev, N.; Forget, F.; Fouchet, T.; Vlasov, P.; Bergeron, G.; Young, R. M. B.; Millour, E.; Fan, S.; Tran, H.; Shakun, A.; Grigoriev, A.; et al.
Abstract: The Atmospheric Chemistry Suite (ACS) onboard the ExoMars Trace Gas Orbiter monitors the Martian atmosphere through different spectral intervals in the infrared light. We present a retrieval algorithm tailored to the analysis of spectra acquired in nadir geometry by Thermal InfraRed channel in honor of professor Vassilii Ivanovich Moroz (TIRVIM), the thermal infrared channel of ACS. Our algorithm simultaneously retrieves vertical profile of atmospheric temperature up to 50 km, surface temperature, and integrated optical depth of dust and water ice clouds. The specificity of the TIRVIM data set lies in its capacity to resolve the diurnal cycle over a 54 sol period. However, it is uncertain to what extent can the desired atmospheric quantities be accurately estimated at different times of day. Here we first present an Observing System Simulation Experiment (OSSE). We produce synthetic observations at various latitudes, seasons and local times and run our retrieval algorithm on these synthetic data, to evaluate its robustness. Different sources of biases are documented, in particular regarding aerosol retrievals. Atmospheric temperature retrievals are found robust even when dust and/or water ice cloud opacities are not well estimated in our OSSE. We then apply our algorithm to TIRVIM observations in April–May 2018 and perform a cross‐validation of retrieved atmospheric temperature and dust integrated opacity by comparisons with thousands of colocated Mars Climate Sounder (MCS) retrievals. Most differences between TIRVIM and MCS atmospheric temperatures can be attributed to differences in vertical sensitivity. Daytime dust opacities agree well with each other, while biases are found in nighttime dust opacity retrieved from TIRVIM at this season. Plain Language Summary: The Martian surface and atmosphere undergo strong variations in temperature and amount of aerosols (dust or water ice cloud particles). Our knowledge on their variations at diurnal scale is however limited, due to lack of appropriate observations. We present a method to analyze thermal emission spectra of Mars' surface and atmosphere recorded by Thermal InfraRed channel in honor of professor Vassilii Ivanovich Moroz (TIRVIM), a spectrometer onboard the ExoMars Trace Gas Orbiter. We have developed a program to derive surface and atmospheric temperatures from these spectra, along with an estimation of the amount of aerosols. The specificity of the TIRVIM data set is its capacity to resolve the diurnal cycle over a 54 sol period. However, atmospheric quantities cannot be accurately estimated at all times of day. One of the goals of our paper is to assess the robustness of our algorithm with the help of simulated observations. The retrieval of aerosol opacity is assessed to be challenging at some times of day, but atmospheric temperature is well determined. We have then applied our algorithm to tens of thousands of TIRVIM observations obtained in April–May 2018 and showed that our derived atmospheric temperatures compare very well with independent measurements obtained from the Mars Climate Sounder, reinforcing our confidence in our method. Key Points: We exploit Thermal InfraRed channel in honor of professor Vassilii Ivanovich Moroz (TIRVIM) spectra to determine Martian atmospheric, surface temperature, as well as integrated opacity of dust and water ice clouds Different sources of biases are investigated with the help of simulated observations at different local times, latitudes and seasons Atmospheric temperatures retrieved from TIRVIM in April–May 2018 are in excellent agreement with colocated Mars Climate Sounder observations